Boot-insole effects on comfort and plantar loading at the heel and fifth metatarsal during running and turning in soccer. Issue 8 (17th April 2016) - Nunns, Michael P I; Dixon, Sharon J; Clarke, James; Carré, Matt
Abstract: Plantar loading may influence comfort, performance and injury risk in soccer boots. This study investigated the effect of cleat configuration and insole cushioning levels on perception of comfort and in-shoe plantar pressures at the heel and fifth metatarsal head region. Nine soccer academy players (age 15.7 ± 1.6 years; height 1.80 ± 0.40 m; body mass 71.9 ± 6.1 kg) took part in the study. Two boot models (8 and 6 cleats) and two insoles (Poron and Poron/gel) provided four footwear combinations assessed using pressure insoles during running and 180° turning. Mechanical and comfort perception tests differentiated boot and insole conditions. During biomechanical testing, the Poron insole generally provided lower peak pressures than the Poron/gel insole, particularly during the braking step of the turn. The boot model did not independently influence peak pressures at the fifth metatarsal, and had minimal influence on heel loads. Specific boot-insole combinations performed differently ( P  < 0.05). The 8-cleat boot and the Poron insole performed best biomechanically and perceptually, but the combined condition did not. Inclusion of kinematic data and improved control of the turning technique are recommended to strengthen future research. The mechanical, perception and biomechanical results highlight the need for a multi-faceted approach in the assessment of footwear.